Mercury Concentration in Liver Tissues of South American Fur Seals (Arctocephalus australis) from Southwestern Atlantic Ocean - Lima, Guilherme S. [UNESP]; Menegario, Amauri A. [UNESP]; Sulato, Everton T. [UNESP]; Pedrobom, Jorge H. [UNESP]; Torres-Florez, Juan P.; Araujo Junior, Marcus A. G. de; Barreto, Andre S. (Soc Brasileira Quimica, 2022)
Mercury (Hg) contamination of oceans is rapidly increasing, however Hg bioaccumulation in pinnipeds has been understudied. Here, we report for the first time Hg concentration in liver tissues of South American fur seals (Arctocephalus australis) in South and Southeast Brazil. Hg concentration was determined in twenty-five fur seals' specimens found stranded along the coast of the Southwestern Atlantic Ocean. Samples were digested using the microwave technique and quantified by cold vapor generation atomic fluorescence spectrometry technique. The average Hg concentration was 6.37 mg kg(-1) (wet weight), with a minimum concentration of 0.09 mg kg(-1) and the highest concentration of 15.58 mg kg(-1). No correlation between biological variables (sex, total length and weight) and Hg concentration in A. australis liver were found. The results presented here are of great importance to establish baselines for future evaluations of Hg contamination in marine mammals and the effects of this environmental problem in animal health.
Keywords: Mercury determination; Marine mammals; Strandings; Bioaccumulation; CV-AFS